Impacts of Wetland Reclamation for Housing Development: Balancing Urban Growth, Environmental Sustainability, and Social Equity - Sebastian, Robert Pedro (International Enterprise Integration Association, 2024)
This research investigates the impacts of wetland reclamation for housing development, focusing on the complex interplay between urban expansion, environmental sustainability, and social equity. As urban populations continue to grow, the demand for housing often leads to the conversion of vital wetland ecosystems into residential and commercial areas. The study employs a multi-method approach, including case studies, stakeholder interviews, and environmental assessments, to evaluate both the positive and negative consequences of this practice. Findings indicate that while wetland reclamation can alleviate housing shortages and stimulate local economies, it incurs significant environmental costs, such as biodiversity loss, increased flooding risks, and degraded water quality. Socially, the displacement of vulnerable communities and the exacerbation of social inequalities are notable consequences of this practice. Furthermore, the research highlights the inadequacies of existing legal and policy frameworks governing wetland reclamation, calling for stronger enforcement and integrated approaches to land-use planning. By recognizing wetlands as essential resources that contribute to ecological health and community resilience, this research underscores the importance of adopting holistic strategies that balance urban growth with environmental stewardship and social responsibility.